Theta/Beta Ratio Neurofeedback Effects on Resting and Task-Related Theta Activity in Children with ADHD - Enriquez-Geppert, Stefanie; Krc, Jaroslav; van Dijk, Hanneke; deBeus, Roger J; Arnold, L Eugene; Arns, Martijn (Applied psychophysiology and biofeedback, 2024)
The EEG theta band displays distinct roles in resting and task states. Low resting theta and transient increases in frontal-midline (fm) theta power during tasks are associated with better cognitive control, such as error monitoring. ADHD can disrupt this balance, resulting in high resting theta linked to drowsiness and low fm-theta activity associated with reduced cognitive abilities. Theta/beta ratio (TBR) neurofeedback aims to normalize resting state activity by downregulating theta, which could potentially unfavorably affect task-related fm-theta. This study examines the TBR neurofeedback's impact on both resting and fm-theta activity, hypothesizing that remission depends on these effects. We analyzed data from a multi-center, double-blind randomized controlled trial with 142 children with ADHD and high TBR (ICAN study). Participants were randomized into experimental or sham NF groups. EEG measurements were taken at rest and during an Oddball task before and after neurofeedback, assessing global electrodes for resting theta and fm electrodes during error dynamics. Post-intervention changes were calculated as differences, and ANOVAs were conducted on GROUP, REMISSION, and CONDITION variables. Final analysis included fewer participants for all analyses. Resting state analysis showed no significant effects on global or fm-theta after TBR neurofeedback. Error dynamics analysis was inconclusive for global and fm-theta in both remitters and non-remitters. Results suggest that the current TBR neurofeedback protocol did not reduce aberrant resting state theta, and emphasize the need for refined protocols targeting specific theta-band networks to reduce resting-state theta without affecting fm-theta related to cognitive control.
Keywords: ICAN study; Task-related and resting state theta; Theta–beta ratio neurofeedback; Error-related dynamics; Fm-theta; Children with ADHD